Novel GUCY2C variant causing familial diarrhea in a Mennonite kindred and a potential therapeutic approach. Issue 7 (5th May 2021) - Wolfe, Rachel M.; Mohsen, Al‐Walid; Walsh Vockley, Cate; Bertrand, Carol A.; Nicholls, Robert D.; Heiman, Paige; Seibold, Leah M.; Vockley, Jerry; Ghaloul‐Gonzalez, Lina
Abstract: Guanylate cyclase 2C (GC‐C), encoded by the GUCY2C gene, is implicated in hereditary early onset chronic diarrhea. Several families with chronic diarrhea symptoms have been identified with autosomal dominant, gain‐of‐function mutations in GUCY2C . We have identified a Mennonite patient with a novel GUCY2C variant (c.2381A > T; p.Asp794Val) with chronic diarrhea and an extensive maternal family history of chronic diarrhea and bowel dilatation. Functional studies including co‐segregation analysis showed that all family members who were heterozygous for this variant had GI‐related symptoms. HEK‐293 T cells expressing the Asp794Val GC‐C variant showed increased cGMP production when stimulated with Escherichia coli heat‐stable enterotoxin STp (HST), which was reversed when 5‐(3‐Bromophenyl)‐5, 11‐dihydro‐1, 3‐dimethyl‐1H‐indeno[2′, 1′:5, 6]pyrido[2, 3‐d]pyrimidine‐2, 4, 6(3H)‐trione (BPIPP; a GC‐C inhibitor) was used. In addition, cystic fibrosis transmembrane conductance regulator (CFTR) activity measured with SPQ fluorescence assay was increased in these cells after treatment with HST, indicating a crucial role for CFTR activity in the pathogenesis of this disorder. These results support pathogenicity of the GC‐C Asp794Val variant as a cause of chronic diarrhea in this family. Furthermore, this work identifies potential candidate drug, GC‐C inhibitor BPIPP, to treat diarrhea caused by this syndrome.